Quo Vadis of Expiration Claims in Indonesian Labor Law: A Corporate Perspective - Amboro, Yudhi Priyo; Tan, Winsherly; Syarief, Elza (UNISSULA, 2025)
Verdict of Indonesian Constitutional Court No. 100 / PUU-X / 2012 and No. 114 / PUU-XIII / 2015 raises the new values in the expiration claims in the field of labor. This study aims to reveal the description of the new values that applicate at the dogmatic level related to the expiration claims after the Indonesian Constitutional Court Verdict No. 100 / PUU-X / 2012 and No. 114 / PUU-XIII / 2015 on the corporate perspective. This study uses normative juridical research, by analyzing secondary data obtained, including related legislation and court Verdicts. The results of this study are: there still found inconsistencies in the level of implementation of the cases which related to the expiration claim in the labor law, that causes legal uncertainty. This inconsistency is influenced by the philosophical basis used by the Indonesian Constitutional Court to decide the Indonesian Constitutional Court's Verdict No. 100 / PUU-X / 2012 and No. 114 / PUU-XIII / 2015. It is necessary and immediate to change the law related to the regulation of the expiration claims in the field of labor that prioritizing the principle of the good faith to see the interests of all parties in employment.